Anorexia in Childhood - Ekaterina Zenia (Journal of Global Pharma Technology, 2020)
Over the past three decades, there has been a tendency to shift anorexia nervosa towards a younger age. It is necessary to identify a possible relationship between mental illness and the presence of anorexia. The purpose of the study is to comparatively examine the clinical, gastroenterological and psychopathological features of the development of anorexia nervosa in children with diagnosed mental disorders (autism, childhood schizophrenia). In 2008-2018, at the base of the Moscow Scientific Center for Mental Health and the Children's Psychiatric Clinic No. 6 (Russian Federation), 167 patients were selected, divided into two groups according to the diagnosis. The first included 90 children with a diagnosis of autism, the second - 77 children with a diagnosis of childhood schizophrenia. Children were observed from 3 months of age until they reach 10 years of age. At 8 years old, the children underwent gastroenterological examination. The frequency of occurrence of deviations in eating behavior was recorded. Used abdominal ultrasound, as well as esophagogastroduodenoscopy. In the group of children with autism aged 8-10 years, the total number of eating disorders is gradually decreasing, 2-2.5 times less than 1-3 years (p = 0.001). The incidence rate of anorexia was 70%. Also recorded a decrease in the frequency of occurrence of violations. At 1-3 years on average, the frequency of occurrence of eating disorders was at the level of one third of cases. At the age of 8-10 years, this indicator decreased by 6-15 times (p = 0.001). In the second group, children with schizophrenia, the manifestation of eating disorders occurs later, at 4-6 months of life. By 1-3 years, the frequency of occurrence of deceleration of chewing and swallowing increases 2 times (p = 0.05). At 8-10 years, these eating disorders develop into persistent phobias. Anorexia is recorded in 90% of cases. At 1-3 years of age, eating behavior changes: bulimia and vomitomania appear. The consequence of this is a decrease in body weight. Despite the fact that at the age of 8-10 years in the second group, many disorders are 2-4 times less likely (p = 0.001) than at 1-3 years, some (bulimia) can remain with the same frequency. Esophagitis and reflux in the esophagus are 3–7 times more likely to occur compared to cardia and erosion (p = 0.05 and p = 0.001). Gastroduodenitis and reflux were most often diagnosed in the stomach, 2 times more often than gastritis (p = 0.05), 6 times more often than erosion (p = 0.001), 10 times more than mucosal proliferation. Damage was found to occur to the gastrointestinal tract in children with anorexia nervosa in almost all of its departments. A group of patients with autism has a high percentage of anorexia (70%), with a predominance of eating disorders such as active or passive refusal to eat. In the group of patients with schizophrenia, anorexia is more common (90%), but eating disorders, edible substances, vomitomania, bulimia dominated among eating disorders. Gastroenterological examination revealed a number of diseases of the gastrointestinal tract, among which esophagitis (37%), gastroduodenitis (41%) and reflux (47%) predominated. The revealed age-related features of the development of eating disorders will allow establishing the disease in time and taking measures to cure it.Keywords: Anorexia nervosa, Autism, Schizophrenia, Bulimia, Womitomania, Eating disorders.